New experimental measurements of the H2-CO2 Collision-Induced Absorption in the [3907, 4770] cm−1 spectral range from 241 to 498 K - F. Vitali; S. Stefani; G. Piccioni; H. Tran; M. Snels; D. Grassi; C. Boulet; D. Biondi; A. Boccaccini (Icarus, 2026)

Vis/NIR spectroscopy and chemometrics for enzymatic softening prediction in quince fruit - Reza Akbari; Tarahom Mesri Gundoshmian; Mohammad Tahmasebi; Mahsa S. Razavi; Irene Locatelli; Silvia Grassi (Postharvest Biology and Technology, 2026)

Effects of antibiotics and metals on meiofauna assessed through taxon/functional and modeling tools: a case study of amoxicillin and copper - Sahar Ishak; Samir Ghannem; Renad M. Alotaibi; Rahaf S. Alkatheri; Mona F. Alharbi; Alanood M. Almutrif; Eleonora Grassi; Federica Semprucci; Riadh Badraoui; Sunakbaeva Dilara; Naoufel Ben Hamadi; Lotfi Khezami; et al. (Marine Pollution Bulletin, 2025)

Multi-instrument sounding of a Jovian thunderstorm from Juno - Shawn R. Brueshaber; Zhimeng Zhang; John H. Rogers; Gerald Eichstädt; Glenn S. Orton; Davide Grassi; Leigh N. Fletcher; Cheng Li; Shinji Mizumoto; Alessandro Mura; Fabiano Oyafuso; Ramanakumar Sankar; et al. (Icarus, 2025)

Accessibility of polycyclic aromatic hydrocarbon content in fishes from the region of the 2019 oil spill on the northeast Brazil coast - Abinoan S. Rodrigues; Thayane Cristina da S. Moreira; Rafael Garrett Dolatto; Jandyson Machado Santos; Marco T. Grassi; Licarion Pinto; Ana Paula S. Paim (Marine Pollution Bulletin, 2025)

Environmental and biological measurements of the anesthetic isoflurane and its possible toxic effects in veterinarians - Tony F. Grassi; Mariane A.P. Silva; Maria V. Destro; Bruno S. De Martinis; Leandro G. Braz; Mariana G. Braz (Environmental Toxicology and Pharmacology, 2025)

Deformed archaeological remains at Lilybaeum in Western Sicily (southern Italy): possible ground signatures of a missed large earthquake - G. Barreca; F. Pepe; A. Sulli; G. Morreale; S. Gambino; M. Gasparo Morticelli; S. Grassi; C. Monaco; S. Imposa (Natural Hazards, 2025)
Archaeoseismic analysis performed in Western Sicily points to deformed archeological remains at Lilybaeum , a Punic coastal city founded in 397 B.C. at the Island’s westernmost edge. Starting from the direct observation of deformed ruins, an interdisciplinary work strategy, which included field-structural analysis, drone-shot high-resolution aerial photogrammetry, and geophysical prospecting, was employed to investigate whether the identified deformations may represent the ground effects of a previously unknown large earthquake in the area. Among the unearthed remains, some mosaics and a stone-paved monumental avenue show evidence of tectonic deformation, being fractured, folded, and uplifted. The trend of folding and fracturing is consistent with the NNW–SSE oriented tectonic max stress axis to which Western Sicily is currently subjected. Displacement along a fracture deforming the Decumanus Maximus together with the finding of a domino-type directional collapse, enable us to interpret the observed deformation as the ground signature of a coseismic slip. The seismic rupture occurred along a previously unmapped deformation front that fits well within the seismotectonic context of Western Sicily. Measured offset, geophysical prospecting, and age-constraints all suggest the possibility that a highly-energetic earthquake nucleated in the area following a coseismic rupture along a NE–SW trending back-verging reverse fault towards the end of the fourth century CE. Since seismic catalogs do not provide evidence of such a large earthquake, this event might represent a missed entry in the historical seismic record. This finding provides constraints to redefine the seismic hazard of Western Sicily, a region where recurrence-time intervals for large earthquakes are still unknown.

Pantropical CO2 emissions and removals for the AFOLU sector in the period 1990–2018 - Sylvia S. Nyawira; Martin Herold; Kalkidan Ayele Mulatu; Rosa Maria Roman-Cuesta; Richard A. Houghton; Giacomo Grassi; Julia Pongratz; Thomas Gasser; Louis Verchot (Mitigation and Adaptation Strategies for Global Change, 2024)
Transparent, accurate, comparable, and complete estimates of greenhouse gas emissions and removals are needed to support mitigation goals and performance assessments under the Paris Agreement. Here, we present a comparative analysis of the agriculture forestry and other land use (AFOLU) emission estimates from different datasets, including National Greenhouse Gas Inventories (NGHGIs), FAOSTAT, the BLUE, OSCAR, and Houghton (here after updated H&N2017) bookkeeping models; Emissions Database for Global Atmospheric Research (EDGAR); and the US Environmental Protection Agency (EPA). We disaggregate the fluxes for the forestry and other land use (FOLU) sector into forest land, deforestation, and other land uses (including non-forest land uses), while agricultural emissions are disaggregated according to the sources (i.e., livestock, croplands, rice cultivation, and agricultural fires). Considering different time periods (1990–1999, 2000–2010, and 2011–2018), we analyse the trend of the fluxes with a key focus on the tropical regions (i.e., Latin America, sub-Saharan Africa, and South and Southeast Asia). Three of the five data sources indicated a decline in the net emissions over the tropics over the period 1990–2018. The net FOLU emissions for the tropics varied with values of 5.47, 5.22, 4.28, 3.21, and 1.17 GtCO 2 year −1 (for BLUE, OSCAR, updated H&N2017, FAOSTAT, and NGHGIs, respectively) over the recent period (2011–2018). Gross deforestation emissions over the same period were 5.87, 7.16, 5.48, 3.96, and 3.74 GtCO 2 year −1 (for BLUE, OSCAR, updated H&N2017, FAOSTAT, and NGHGIs). The net forestland sink was −1.97, −3.08, −2.09, −0.53, and −3.00 GtCO 2 year −1 (for BLUE, OSCAR, updated H&N2017, FAOSTAT, and NGHGIs). Continental analysis indicated that the differences between the data sources are much large in sub-Saharan Africa and South and Southeast Asia than in Latin America. Disagreements in the FOLU emission estimates are mainly explained by differences in the managed land areas and the processes considered (i.e., direct vs indirect effects of land use change, and gross vs net accounting for deforestation). Net agricultural emissions from cropland, livestock, and rice cultivation were more homogenous across the FAOSTAT, EDGAR, and EPA datasets, with all the data sources indicating an increase in the emissions over the tropics. However, there were notable differences in the emission from agricultural fires. This study highlights the importance of investing and improving data sources for key fluxes to achieve a more robust and transparent global stocktake.

How natural and anthropogenic factors should drive microplastic behavior and fate: The scenario of Brazilian urban freshwater - Fernando F. Sodré; Imisi M. Arowojolu; Maria C. Canela; Rodrigo S. Ferreira; Andreia N. Fernandes; Cassiana C. Montagner; Cristiane Vidal; Mariana A. Dias; Gilberto Abate; Leticia C. da Silva; Marco T. Grassi; Crislaine Bertoldi; et al. (Chemosphere, 2023)

Preparation of carbonaceous materials from flotation-sludge of the poultry industry and its application in the methylene blue adsorption - Angélica F. M. Streit; Patrícia Grassi; Fernanda C. Drumm; Luis F. O. Silva; Marcos L. S. Oliveira; Gabriela C. Collazzo; Marcelo Godinho; Daniele Perondi; Guilherme L. Dotto (Environmental Science and Pollution Research, 2023)

Conversion of foliar residues of Sansevieria trifasciata into adsorbents: dye adsorption in continuous and discontinuous systems - Patrícia Grassi; Matias Schadeck Netto; Sérgio Luiz Jahn; Jordana Georgin; Dison S. P. Franco; Mika Sillanpää; Lucas Meili; Luis F. O. Silva (Environmental Science and Pollution Research, 2022)

Novel application of FeIn2S4 as an efficient photo-Fenton catalyst for degradation of Ponceau 4R in aqueous solution - P. Grassi; J. da Silveira Salla; S. L. Jahn; E. L. Foletto (International Journal of Environmental Science and Technology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

A quick combined approach for the characterization of a cliff during a post-rockfall emergency - G. Pappalardo; S. Mineo; S. Imposa; S. Grassi; A. Leotta; F. La Rosa; D. Salerno (Landslides, 2020)

Solid wastes from the enzyme production as a potential biosorbent to treat colored effluents containing crystal violet dye - Patrícia Grassi; Fernanda C. Drumm; Stéfani S. Spannemberg; Jordana Georgin; Denise Tonato; Marcio A. Mazutti; Janaína O. Gonçalves; Marcos L. S. Oliveira; Guilherme L. Dotto; Sérgio L. Jahn (Environmental Science and Pollution Research, 2020)

Application of Beauveria bassiana spore waste as adsorbent to uptake acid red 97 dye from aqueous medium - Jordana Georgin; Eliana Alves; Fernanda Drumm; Denise Tonato; Patrícia Grassi; Jeferson S. Piccin; Marcos L. S. Oliveira; Guilherme L. Dotto; Marcio A. Mazutti (Environmental Science and Pollution Research, 2019)

Potential of Cedrella fissilis bark as an adsorbent for the removal of red 97 dye from aqueous effluents - Jordana Georgin; Dison S. P. Franco; Patricia Grassi; Denise Tonato; Daniel G. A. Piccilli; Lucas Meili; Guilherme L. Dotto (Environmental Science and Pollution Research, 2019)

Study of landslides at the archaeological site of Abakainon necropolis (NE Sicily) by geomorphological and geophysical investigations - G. Pappalardo; S. Imposa; M. S. Barbano; S. Grassi; S. Mineo (Landslides, 2018)

Interannual Variation in Diet, Dietary Diversity, and Dietary Overlap in Three Sympatric Strepsirrhine Species in Southeastern Madagascar - E. M. Erhart; S. R. Tecot; C. Grassi (International Journal of Primatology, 2018)

Geophysical surveys to study a landslide body (north-eastern Sicily) - S. Imposa; S. Grassi; F. Fazio; G. Rannisi; P. Cino (Natural Hazards, 2017)

3D Subsoil Model of the San Biagio ‘Salinelle’ Mud Volcanoes (Belpasso, Sicily) derived from Geophysical Surveys - S. Imposa; S. Grassi; G. De Guidi; F. Battaglia; G. Lanaia; S. Scudero (Surveys in Geophysics, 2016)

Gokyo Khumbu/Ama Dablam Trek 2012: effects of physical training and high-altitude exposure on oxidative metabolism, muscle composition, and metabolic cost of walking in women - E. Tam; P. Bruseghini; E. Calabria; L. Dal Sacco; C. Doria; B. Grassi; T. Pietrangelo; S. Pogliaghi; C. Reggiani; D. Salvadego; F. Schena; L. Toniolo; et al. (European Journal of Applied Physiology, 2016)

Fusarium spp. is able to grow and invade healthy human nails as a single source of nutrients - J. Galletti; M. Negri; F. L. Grassi; É. S. Kioshima-Cotica; T. I. E. Svidzinski (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Assessment of sweet potato [ Ipomoea batatas (L.) Lam] for bioethanol production in southern Italy - A. Montefusco; M. Durante; S. Grassi; G. Piro; G. Dalessandro; M. S. Lenucci (Plant Biosystems, 2014)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)

The European carbon balance. Part 4: integration of carbon and other trace‐gas fluxes - E. D. SCHULZE; P. CIAIS; S. LUYSSAERT; M. SCHRUMPF; I. A. JANSSENS; B. THIRUCHITTAMPALAM; J. THELOKE; M. SAURAT; S. BRINGEZU; J. LELIEVELD; A. LOHILA; C. REBMANN; et al. (Global Change Biology, 2010)
Overviewing the European carbon (C), greenhouse gas (GHG), and non‐GHG fluxes, gross primary productivity (GPP) is about 9.3 Pg yr −1 , and fossil fuel imports are 1.6 Pg yr −1 . GPP is about 1.25% of solar radiation, containing about 360 × 10 18 J energy – five times the energy content of annual fossil fuel use. Net primary production (NPP) is 50%, terrestrial net biome productivity, NBP, 3%, and the net GHG balance, NGB, 0.3% of GPP. Human harvest uses 20% of NPP or 10% of GPP, or alternatively 1‰ of solar radiation after accounting for the inherent cost of agriculture and forestry, for production of pesticides and fertilizer, the return of organic fertilizer, and for the C equivalent cost of GHG emissions. C equivalents are defined on a global warming potential with a 100‐year time horizon. The equivalent of about 2.4% of the mineral fertilizer input is emitted as N 2 O. Agricultural emissions to the atmosphere are about 40% of total methane, 60% of total NO‐N, 70% of total N 2 O‐N, and 95% of total NH 3 ‐N emissions of Europe. European soils are a net C sink (114 Tg yr −1 ), but considering the emissions of GHGs, soils are a source of about 26 Tg CO 2 C‐equivalent yr −1 . Forest, grassland and sediment C sinks are offset by GHG emissions from croplands, peatlands and inland waters. Non‐GHGs (NH 3 , NO x ) interact significantly with the GHG and the C cycle through ammonium nitrate aerosols and dry deposition. Wet deposition of nitrogen (N) supports about 50% of forest timber growth. Land use change is regionally important. The absolute flux values total about 50 Tg C yr −1 . Nevertheless, for the European trace‐gas balance, land‐use intensity is more important than land‐use change. This study shows that emissions of GHGs and non‐GHGs significantly distort the C cycle and eliminate apparent C sinks.

Phylogeographical structure and conservation genetics of wild grapevine - F. Grassi; M. Labra; S. Imazio; R. Ocete Rubio; O. Failla; A. Scienza; F. Sala (Conservation Genetics, 2006)

Chloroplast Microsatellites to Investigate the Origin of Grapevine - S. Imazio; M. Labra; F. Grassi; A. Scienza; O. Failla (Genetic Resources and Crop Evolution, 2006)

Comparison between recombinant baculo- and adenoviral-vectors as transfer system in cardiovascular cells - G. Grassi; H. Köhn; B. Dapas; R. Farra; J. Platz; S. Engel; S. Cjsareck; R. Kandolf; C. Teutsch; R. Klima; G. Triolo; A. Kuhn (Archives of Virology, 2006)

Ex-situ conservation of Black poplar in Europe: genetic diversity in nine gene bank collections and their value for nature development - V. Storme; A. Vanden Broeck; B. Ivens; D. Halfmaerten; J. Van Slycken; S. Castiglione; F. Grassi; T. Fossati; J. E. Cottrell; H. E. Tabbener; F. Lefèvre; C. Saintagne; et al. (Theoretical and Applied Genetics, 2004)

Evidence of a secondary grapevine domestication centre detected by SSR analysis - F. Grassi; M. Labra; S. Imazio; A. Spada; S. Sgorbati; A. Scienza; F. Sala (Theoretical and Applied Genetics, 2003)

Molecular analysis of natural populations of Populus nigra L. intermingled with cultivated hybrids - T. Fossati; F. Grassi; F. Sala; S. Castiglione (Molecular Ecology, 2003)
In this study six simple sequence repeats (SSR or microsatellites) were selected for their ability to fingerprint a total of 60 commercial clones of Populus deltoides Marsh. and Populus × canadensis Moench (typically derived from crosses between Populus nigra L and P. deltoides ) and to characterize a natural population of P. nigra growing along the Ticino river in the North of Italy. Out of six SSRs used, four microsatellite loci were found to have alleles which were species‐specific to P. deltoides and could therefore be used as markers for introgression of P. deltoides into P. nigra . In the studied region hybrid poplars and P. deltoides commercial clones are cultivated as monoclonal stands close to the area where black poplar has its natural habitat. SSR analysis was performed to investigate whether there was evidence of introgression between the natural population and the monoclonal plantations of hybrids and P. deltoides clones cultivated in the surrounding area. Three stages of the natural population were analysed: a group of old trees about a hundred years old, a younger population (aged 2–30 years) and the seedlings of three females of this population. Alleles specific to P. deltoides were detected only in the old cohort of the natural population, while no introgression was observed in the younger individuals and their progenies. These results were also confirmed by isozyme analysis of loci PGI‐B, PGM and LAP‐A, which were previously identified as diagnostic for P. nigra , P. deltoides and P. × canadensis .

Special Contribution: An Overview of Recent Seismic Refraction Experiments in Central Europe - A. Guterch; M. Grad; A. Špičák; E. Brückl; E. Hegedüs; G.R. Keller; H. Thybo; K. Aric; S. Acevedo; I. Asudeh; M. Behm; A. A. Belinsky; et al. (Studia Geophysica et Geodaetica, 2003)

Nefazodone, meta-chlorophenylpiperazine, and their metabolites in vitro: cytochromes mediating transformation, and P450-3A4 inhibitory actions - Lisa L. von Moltke; David J. Greenblatt; Brian W. Granda; Jeffrey M. Grassi; Jürgen Schmider; Jerold S. Harmatz; Richard I. Shader; L. L. von Moltke (Psychopharmacology, 1999)

Gepirone and 1-(2-pyrimidinyl)-piperazine in vitro: human cytochromes mediating transformation and cytochrome inhibitory effects - L. L. von Moltke; D. J. Greenblatt; J. M. Grassi; B. W. Granda; S. M. Fogelman; J. S. Harmatz; S. J. Kramer; L. F. Fabre; R. I. Shader (Psychopharmacology, 1998)